2014
DOI: 10.1177/1060028014529260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bariatric Surgery on Hypertension

Abstract: The results of this meta-analysis indicate that patients who undergo bariatric surgery experience improvement and resolution of their hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 65 publications
(147 reference statements)
4
43
0
2
Order By: Relevance
“…3 Dyslipidemia is common feature in obese patient and major risk factor for development of atherosclerosis and then heart related diseases. 4 Bariatric surgery has proven to be an effective treatment against obesity related comorbidities achieving high rate of remission in disease such as type 2 DM 5,6 or arterial hypertension 7,8 among others. In these cases of dyslipidemia studies have shown acceptable short term outcome after bariatric surgery reaching more than 85% of resolution in one year.…”
Section: Introductionmentioning
confidence: 99%
“…3 Dyslipidemia is common feature in obese patient and major risk factor for development of atherosclerosis and then heart related diseases. 4 Bariatric surgery has proven to be an effective treatment against obesity related comorbidities achieving high rate of remission in disease such as type 2 DM 5,6 or arterial hypertension 7,8 among others. In these cases of dyslipidemia studies have shown acceptable short term outcome after bariatric surgery reaching more than 85% of resolution in one year.…”
Section: Introductionmentioning
confidence: 99%
“…While these procedures restructure the gut in various ways, all of them result in comorbid disease remission including T2DM[1203639108118154162166168171173189193202212213214221224231249265273] and MetS,[7303245121132174177183199225243250260270274275] even if at a variable rate and durability;[12314878828397108114168208221224243244267275] though remission has been reported in a number of publications to be durable[139168178191] and immediate prior to significant weight loss. [2074161187188190195]…”
Section: Bariatric Surgery Impact On Hepatic O2mentioning
confidence: 99%
“…The role of obesity on hypertension development was also confirmed in the studies that showed significant reduction in BP after weight reduction . There are different methods of weight reduction: lifestyle changes, pharmacological intervention, and bariatric surgery . Lifestyle changes such as diet and exercise usually cannot result with clinically significant weight loss .…”
Section: Introductionmentioning
confidence: 88%
“…Pharmacological intervention has not provided satisfactory results so far. Bariatric surgery is an invasive method, but it provides more constant BMI reduction with greater probability of long‐term BP decrease . Even though data regarding long‐term outcomes are lacking, bariatric surgery seems to provide an important renal, cardiovascular, and mortality benefit in obese patients than other types of weight loss …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation